Rancang Bangun Sistem Komunikasi Data Antara Mikrokontroller Atmega8 Dengan Arduino Pada Mesin Roaster Coffe Digital - Rachmad Ikhsan; Effendi Effendi (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2020)
Roasting coffee manually is widely applied by coffee producers. This process takes a very long time and is less efficient in terms of productivity for industry standards. This machine  is equipped with a thermocouple sensor as a temperature sensor that will measure the temperature in the roasting cylinder, then equipped with a timer as a reminder of roasting time that ranges from 15 minutes at a temperature of 200 degrees Celsius, this machine  is also equipped with android as a timer controller on the coffee roaster machine. This machine is also equipped with a microcontroller and Bluetooth as a media transmitter and data receiver. From the test results obtained data that Bluetooth can be used for data communication between the microcontroller and Android with a distance of 30 meters in the room, and 12 meters outside the room. If it exceeds that distance, then Bluetooth will not respond back